2020
DOI: 10.1021/acs.jmedchem.9b01701
|View full text |Cite
|
Sign up to set email alerts
|

The Race to Bash NASH: Emerging Targets and Drug Development in a Complex Liver Disease

Abstract: Nonalcoholic steatohepatitis (NASH) is a severe form of nonalcoholic fatty liver disease (NAFLD) characterized by liver steatosis, inflammation, and hepatocellular damage. NASH is a serious condition that can progress to cirrhosis, liver failure, and hepatocellular carcinoma. The association of NASH with obesity, type 2 diabetes mellitus, and dyslipidemia has led to an emerging picture of NASH as the liver manifestation of metabolic syndrome. Although diet and exercise can dramatically improve NASH outcomes, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 336 publications
0
63
0
Order By: Relevance
“…NAFLD refers to excessive fat deposition in the liver in the absence of ethanol and other clear causes. The main characteristics of this disease are accumulation and diffuse fatty degeneration of hepatocytes (3,4). NAFLD is the most common chronic liver disease (4,5), and NAFLD has become a worldwide public health problem that endangers human health.…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD refers to excessive fat deposition in the liver in the absence of ethanol and other clear causes. The main characteristics of this disease are accumulation and diffuse fatty degeneration of hepatocytes (3,4). NAFLD is the most common chronic liver disease (4,5), and NAFLD has become a worldwide public health problem that endangers human health.…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine the expression characteristics of disease-related clinically significant genes in different cell types/subtypes, we analyzed the gene expression of a series of blood markers and drug targets for NASH diagnosis and therapy in each cell type. Cytokeratin 18 (CK18) is a blood marker of apoptosis and fibrosis for diagnosis of NASH (40). We found that Krt18 , which encodes CK18, is specifically high expressed in cholangiocytes and obviously increased in subtype Cho3 in HF-MCD group (Supplementary Figure S5E and F), suggesting that NASH is accompanied by significant injury and apoptosis of cholangiocytes, especially subtype Cho3, and cholangiocytes may associate with the mechanism of NASH.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, no specific drug has been approved for clinical use to treat patients with NASH. There are many promising candidates in the drug development pipeline, and some have shown very useful for improving NASH by controlling inflammation in clinical trials (Table 2), such as dual CCR2/5 inhibitor, apoptosis signal-regulating kinase 1 (ASK1) inhibitor, and caspase inhibitor (Romero et al, 2020). Unfortunately, the latest clinic outcomes of selonsertib (an ASK1 inhibitor) and emricasan (a pan-caspase inhibitor) are not satisfied (Loomba et al, 2018;Harrison et al, 2020;Ratziu et al, 2020;Romero et al, 2020).…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%